(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extract of whole plant of Sida rhombifolia and different fractions generated from it were tested for membrane stabilizing and thrombolytic activities. In hypotonic solution- and heat-induced conditions, the chloroform soluble partitionates inhibited haemolysis of human erythrocyte by 22.11±0.14% and 64.71±0.08%, respectively as compared to 71.97±0.51% and 40.12±0.29% demonstrated by the standard acetyl salicylic acid (ASA). Moreover, the pet ether soluble materials revealed highest thrombolytic activity with clot lysis value of 19.51±0.03% as compared to 66.98±0.11% exhibited by the standard streptokinase. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22313 Bangladesh Pharmaceutical Journal 17(1): 43-45, 2014